Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

Data-driven investigation of ship fuel consumption integrating causal inference and hierarchical analysis - Wenjie Cao; Xinjian Wang; Wei Zhang; Huanhuan Li; Siming Fang; Zaili Yang (Transportation Research Part D: Transport and Environment, 2026)

A physics-informed transformer framework for multi-step 6-DOF motion prediction of distressed vessels - Yingjie Yu; Xiufeng Zhang; Siming Zhang; Mingjie Li (Ocean Engineering, 2026)

Ultrasound-assisted complexation of Millettia speciosa by-product protein with polyphenols: improved structural properties, antioxidant and hypoglycemic activities, and gut microbiota modulation - Meng Wang; Jiexi Li; Feng Li; Yebao Chen; Fangfang Ban; Hua Yang; Siming Zhu; Dan Xu; Junlin Wu (Food Chemistry, 2026)

Corrigendum to “Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater” [Bioresour. Technol. 459 (2026) 135175] - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

Engineering lignin-incorporated hydrogels for agricultural and environmental applications: From synthesis to sustainable implementation - Fuke Ai; Xiaolei Zhang; Bing Hu; Shin Ying Foong; Weidong Ye; Yameng Li; Quanguo Zhang; Pedram Fatehi; Siming You; Zhiping Zhang (Bioresource Technology, 2026)

Dynamic modeling of submarine cable laying using ALE-ANCF: Insights into cable tension and configuration - Wenyan Gu; Xiangqian Zhu; Xinyu Li; Yanliang Pei; Jinsheng Zhang; Siming Yang; Zhixun Yang (Ocean Engineering, 2026)

MPM-DEM simulation of woody debris flow interaction with slit-check dams - Liu Ming; Xiaoqin Lei; Xinpo Li; Siming He; Xiaojun Guo; Liangliang Wang (Journal of Hydrology, 2026)

A hierarchical hybrid flood modeling framework: deconstructing runoff response into initiation states and generation processes - Tao Xie; Lu Chen; Bin Yi; Zhiyuan Leng; Siming Li; Yazhong Wu; Deming Zhu (Journal of Hydrology, 2026)

Stability of oil bodies under pulsed electric field exposure to rapeseed: New insights into improving oil extraction capacity - Qiqi Zhang; Jinling Hu; Yunyun Li; Bo Wang; Jing Wang; Jie Zhao; Siming Zhao; Caihua Jia; Jie Kuai; Guangsheng Zhou (Food Chemistry, 2026)

Corrigendum to “A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall” [J. Hydrol. 673 (2026) 135352] - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

Plant-derived CTLA-4-targeting miR152 via lipid nanoparticles potentiates doxorubicin efficacy in breast cancer immunochemotherapy - Hanyi Ye; Wei Jin; Yifan Feng; Ze Wu; Shuhui Sun; Mengyao Cui; Shun Lv; Bing Jin; Chang Liu; Siming Wang; Ying Li; Zhengqi Dong (Science China Life Sciences, 2026)

Illumination-induced restructuring of extracellular polymeric substances from Klebsiella Sp. HDJY-1 drives indirect photodegradation of thifensulfuron-methyl - Jiaying Gu; Yaqi Jiao; Chunnan Zhou; Junxin Jia; Siming Li; Kai Wang; Hui Li; Hongtao Shi; Qin Zhou; Rong Liu; Li Li (Water Research, 2026)

A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

Increased microbiological risks caused by extreme precipitation in a drinking water system in mountainous area: From source to tap - Xinyan Xiao; Chen Cheng; Xiuxiu Wang; Ziqi Luo; Lihua Li; Siming Hu; Dongmei Zhu; Mingbao Feng; Chengsong Ye; Xin Yu (Journal of Hazardous Materials, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics” [Food Chem. 513 (2026) 149020] - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

A numerical study of the transition process from rock-ice avalanche to debris flow - Wei Liu; Benhong Xiang; Jihao Jian; Siming He; Lanhai Li (Landslides, 2026)

Fine-scale mangrove species monitoring and ecological threshold assessment for coastal management in Quanzhou Bay, China - Siming Chen; Fei Chen; Longhui Niu; Zhong Deng; Kebin Wu; Wenbin Li (Environmental Monitoring and Assessment, 2026)

Efficient simulation of landslide-induced surges and control effects of different position piles based on an improved flow-flow model - Zhangqing Wang; Yong Wu; Yongjie Zhao; Yingpeng Wang; Siming He; Xinpo Li; Lei Zhu (Journal of Hydrology, 2026)

Growth rate influences flavour formation in Lactococcus cremoris independently of metabolic protein levels - Avis Dwi Wahyu Nugroho; Berdien van Olst; Douwe Molenaar; Siming Li; Adriano Guiso; Sjef Boeren; Michiel Kleerebezem; Herwig Bachmann (International Journal of Food Microbiology, 2026)

3D MPM simulation of the coseismic Daguangbao landslide with a state-dependent frictional weakening model - Xiaoqin Lei; Lei Zhu; Siming He; Xinpo Li; Liu Ming; Yu Luo (Landslides, 2026)

Effects of isolation layer on the segmental tunnel transiting soil-rock strata under transverse excitation - Yong Yuan; Siming Li; Mingqing Xiao; Haitao Yu; Roberto Cudmani (Soil Dynamics and Earthquake Engineering, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Optimization on escape exit selection for personnel in highway tunnel fires - Jinghong Wang; Jintao Li; Hongcheng Lu; Siming Wang; Ran Ye; Jialin Wu (Tunnelling and Underground Space Technology, 2026)

Segmental tunnel with isolation layer in soil-rock transition under longitudinal excitation: experimental and numerical investigation - Siming Li; Yong Yuan; Roberto Cudmani; Jinghua Zhang; Mingqing Xiao; Haitao Yu (Transportation Geotechnics, 2026)

Seismic response of segmental tunnel in soil-rock strata under longitudinal excitation: experimental and numerical analysis - Siming Li; Yong Yuan; Haitao Yu; Jinghua Zhang; Mingqing Xiao; Roberto Cudmani (Soil Dynamics and Earthquake Engineering, 2026)

Okadaic acid induces oxidative stress and immunotoxicity in zebrafish: involvement of the p53 pathway and behavioral alterations - Duo Chen; Siming Pan; Jiapeng Wang; Zhenlu Li; Chenhuan Dong; Yuanxin Liang; Yilin Huang; Youqiang Chen; Ting Xue; Chentao Lin (Fish & Shellfish Immunology, 2026)

Revealing long-term runoff mechanisms using the deep learning model interpretable framework driven by global and local information - Binlin Yang; Lu Chen; Siming Li; Bin Yi; Nengjie Hu (Journal of Hydrology, 2025)

Microbial electrochemical reduction of chromate in groundwater driven by Thiobacillus denitrificans - Luyao Wang; Siming Chen; Song Wang; Xinxin Li; Baogang Zhang (Journal of Environmental Chemical Engineering, 2025)

Cellulose-engineered janus periosteum with compartmentalized angiogenic and osteo-immunomodulatory abilities for bone regeneration - Wuyan Xu; Kun Liu; Jiaqing Chen; Junliang Liu; Siming Li; Hua Wang; Binghong Luo; Qingqi Meng (Carbohydrate Polymers, 2025)

Corrigendum to “Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region”. [Catena 260 (2025) 109423] - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

Methionine in embryonic development: metabolism, redox homeostasis, epigenetic modification and signaling pathway - Chang Yan; Biyan He; Chenjun Wang; Wanzhen Li; Siming Tao; Jingqing Chen; Yuquan Wang; Ling Yang; Yingjie Wu; Zhenlong Wu; Ning Liu; Yinghe Qin (Critical Reviews in Food Science and Nutrition, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

Interaction mechanism and structure-activity relationship of hesperidin, methyl hesperidin and hesperidin methyl chalcone with ovalbumin: A comparative study - Xuefei Wen; Xinpeng Li; Siming Zhu; Liang Chen; Zhendong Wang; Ming Yu; Zhanhua Deng (Food Chemistry, 2025)

Bioinspired ECM-specific microenvironment scaffold: A multi-biomimetic strategy spatially guides osteochondral regeneration - Kun Liu; Wuyan Xu; Lin Li; Wendong Zhang; Wei Wen; Shan Ding; Mingxian Liu; Changren Zhou; Siming Li; Qingqi Meng; Binghong Luo (Chemical Engineering Journal, 2025)

A Dynamic Time-varying Distributed Unit Hydrograph Considering the Heterogeneity of Runoff Generation - Bin Yi; Lu Chen; Binlin Yang; Zhiyuan Leng; Siming Li; Tao Xie (Water Resources Management, 2025)

Novel metabolic pathways of bioelectrochemical vanadate reduction by Thiobacillus denitrificans without exogenous electron donor supplementation in groundwater - Luyao Wang; Siming Chen; Rui Li; Baogang Zhang (Water Research, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Study on the influence of 3D pre-existing joint on rockfall fragmentation during impact based on discrete element method - Yongjie Zhao; Yong Wu; Yingpeng Wang; Siming He; Xinpo Li; Lei Zhu; Zhangqing Wang (Computers and Geotechnics, 2025)

Decreasing the pH value would improve the swallowing characteristics of whey protein isolate-enriched thickened fluids for dysphagia populations - Zihang Cheng; Kedu Wang; Dongling Qiao; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Incorporating maltitol regulates the gel properties and structural features of κ-carrageenan-corn starch-soy protein isolate based quaternary system and its application of low glycemic index gummies - Xiaowen Pi; Lilin Zhu; Mengqian Xiang; Siming Zhao; Bowen Li; Dongling Qiao; Binjia Zhang (Food Chemistry, 2025)

Catalytic-difference elucidating of hesperidin and naringin by Rhamnosidase and prunin production enhancing through enzyme mutation - Xinpeng Li; Ping Chen; Lin Chen; Sheng Gao; Zhendong Wang; Siming Zhu (Food Bioscience, 2025)

An integrated non-alkaline derivatization strategy using 2,2′-dithiodipyridine and HPLC for simultaneous analysis of total and low-molecular-weight free thiols in human serum - Zhiyu Shao; Jie Zeng; Jun Dong; Fusui Ji; Hongxia Li; Ruiyue Yang; Wenxiang Chen; Wenyu Li; Siming Wang (Analytica Chimica Acta, 2025)

Germination and fermentation synergistically tailor the starch structure within brown rice and the quality features of brown rice tea - Yabin Guo; Yang Xu; Siming Zhao; Dongling Qiao; Bowen Li; Binjia Zhang (Food Research International, 2025)

Encapsulated benzoic acid alleviated LPS-induced intestinal damage via NRF2 activation - Yanyan Zhang; Tianjiao Wang; Qing He; Mahmoud M. Abouelfetouh; Qin Fu; Siming Yao; Shiqiang Ju; Zhenlei Zhou; Qiao Li (Food Bioscience, 2025)

Wheat bran insoluble fiber with varying particle distributions orchestrates microbial metabolism to counteract obesity and hyperlipidemia - Kexin Niu; Bingqian Yang; Lu Gan; Meng Niu; Kaikai Li; Siming Zhao (Food Bioscience, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Genetic analysis and fine mapping reveal that AhRt3, which encodes an anthocyanin reductase, is responsible for red testa in cultivated peanuts - Yanyan Tang; Xiantao Zhou; Xin Li; Cai Zhou; Wenlin Wang; Mo Zhou; Zhicheng Hu; Xiaobei Li; Kaiyuan Zhang; Siming Wang; Zhihao Zhang; Hao Chen; et al. (Theoretical and Applied Genetics, 2025)

Isolation and identification of native microalgae from the Yellow River Delta: A dual-focus study on the tolerance assessment of microalgae and their growth enhancement on Sesbania cannabina under saline-alkali stress - Xiao Yu; Siming Li; Jiahao Liang; Shenkun Liu; Yinchu Wang; Jianchao Yang; Chenggang Ren; Chunli Ji; Hongli Cui; Song Qin (Algal Research, 2025)

Artificial intelligence in plastic recycling and conversion: A review - Yi Fang; Yuming Wen; Leilei Dai; Chi-Hwa Wang; Siming You; Wangliang Li (Resources, Conservation and Recycling, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Machine learning-assisted life cycle assessment of biochar soil application - Yize Li; Rohit Gupta; Wangliang Li; Yi Fang; Jaime Toney; Siming You (Journal of Cleaner Production, 2025)

Integrative transcriptomic, proteomic and metabolomic analyses yields insights into muscle fiber type in cattle - Xiaofan Tan; Ruixue Zhao; Jing Chen; Zhiwei Yan; Xin Sui; Heling Li; Qiao Li; Xuehai Du; Yangzhi Liu; Siming Yao; Ying Yang; David M. Irwin; et al. (Food Chemistry, 2025)

Swelling than diffusion behavior of starch under protein crowding conditions affects the texture of the protein/starch blend gels - Xuxu Li; Mingcong Fan; Qilin Huang; Siming Zhao; Shanbai Xiong; Dapeng Li (Food Hydrocolloids, 2025)

Non-local μ(I) rheology improves landslide deposition modeling in MLS-MPM simulations - Shuxi Zhao; Yang Liu; Gianvito Scaringi; Xinpo Li; Siming He; Gang He; Lei Zhu (Engineering Geology, 2025)

An investigation on traction for deep-sea mining vehicle considering the interference effect between adjacent grousers - Mingshuai Xi; Fei Sha; Yuhang Zuo; Jingze Xu; Siming Zhang; Zeqian Li (Ocean Engineering, 2025)

The development of thickened fermented rice milk formulation for people with dysphagia: A view of multiple in vitro simulation methods - Zexue Lin; Lingling Ma; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Effect of bisphenol F on reproductive function in F1 generation male mice and its potential mechanisms - Bo Li; Siming Huo; Jiayu Du; Xuliang Zhang; Jian Zhang; Miao Song; Yanfei Li (Environmental Pollution, 2025)

Understanding the application-related features of sweet potato starch varying in multi-scale supramolecular structure - Yabin Guo; Dongling Qiao; Siming Zhao; Xiaowen Pi; Bowen Li; Kai Zhang; Binjia Zhang (Carbohydrate Polymers, 2025)

Effects of microplastics separate exposure and co-exposure to 17β-estradiol on the productive performance of juvenile female Chinese mitten crab (Eriocheir sinensis) - Yang Fu; Jian Zhang; Yilong Cui; Bo Li; Siming Huo; Jiayu Du; Yanfei Li (Science of The Total Environment, 2024)

Neurotoxic effects of perinatal exposure to Bisphenol F on offspring mice - Siming Huo; Bo Li; Jiayu Du; Xuliang Zhang; Miao Song; Yanfei Li (Environmental Pollution, 2024)

Untargeted metabolomics to detect and identify plasma metabolic signatures associated with intracranial aneurysm and its rupture - Siming Gui; Jia Jiang; Dingwei Deng; Dachao Wei; Xiheng Chen; Yudi Tang; Jian Lv; Wei You; Ting Chen; Yang Zhao; Hengwei Jin; Xinke Liu; et al. (Metabolic Brain Disease, 2024)

Evaluating the impact of improved filter-wrapper input variable selection on long-term runoff forecasting using local and global climate information - Binlin Yang; Lu Chen; Bin Yi; Siming Li (Journal of Hydrology, 2024)

Escherichia coli heat-labile enterotoxin B subunit as an adjuvant of mucosal immune combined with GCRV-II VP6 triggers innate immunity and enhances adaptive immune responses following oral vaccination of grass carp (Ctenopharyngodon idella) - Jiyuan Yin; Huiliang Wu; Wei Li; Yingying Wang; Yingying Li; Xubing Mo; Siming Li; Yan Ren; Houjun Pan; Peng Jiang; Qing Wang (Fish & Shellfish Immunology, 2024)

The toxic effects and mechanisms of maternal exposure to Bisphenol F during gestation and lactation on lungs in female offspring mice - Jiayu Du; Siming Huo; Bo Li; Xuliang Zhang; Jian Zhang; Yang Fu; Bing Shao; Yanfei Li; Miao Song (Environmental Pollution, 2024)

Advancements and future perspectives in the study of oligosaccharides derived from edible-medicinal mushrooms - Shuo Wang; Jiajie Qi; Xiaoming Cai; Weijie Wu; Zhuo A. Wang; Siming Jiao; Caihong Dong; Yi Li; Zhenquan Yang (Food Bioscience, 2024)

Comparing carbon-saving potential of the pyrolysis of non-recycled municipal plastic waste: Influences of system scales and end products - Bauyrzhan Biakhmetov; Yue Li; Qunshan Zhao; Yong Sik Ok; Abay Dostiyarov; Young-Kwon Park; David Flynn; Siming You (Journal of Cleaner Production, 2024)

Comparison and inhibition mechanism study on the in vitro digestibility of rice starch complex with soy β-conglycinin and soy glycinin - Xin Shi; Xuxu Li; Ruifeng Wang; Meng Niu; Siming Zhao (Food Hydrocolloids, 2024)

Activation of the NLRP3-CASP-1 inflammasome is restrained by controlling autophagy during Glaesserella parasuis infection - Chaoxiong Yue; Jinquan Li; Siming Zhang; Ruyi Ma; Mingjiao Suo; Yiwen Chen; Hui Jin; Yan Zeng; Yushan Chen (Veterinary Microbiology, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Investigating the dynamic process of a rock avalanche through an MLS-MPM simulation incorporated with a nonlocal μ(I) rheology model - Shuxi Zhao; Siming He; Xinpo Li; Gianvito Scaringi; Yang Liu; Yu Deng (Landslides, 2024)

Unveiling the inverse antimicrobial impact of a hetero-chitooligosaccharide on Candida tropicalis growth and biofilm formation - Yangyang Liu; Ruilian Li; Yuchen Zhang; Siming Jiao; Tong Xu; Yuhang Zhou; Yujing Wang; Jinhua Wei; Wei Du; Morihisa Fujita; Yuguang Du; Zhuo A. Wang (Carbohydrate Polymers, 2024)

Long-term use of etomidate disrupts the intestinal homeostasis and nervous system in mice - Siming Ding; Kan Li; Xing Han; Wenting Lin; Yingjun Qin; Renjuan Cao; Yuan Ren (Toxicology, 2024)

Corrigendum to “Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage” [Food Chem. Toxicol. 178 (2023) 113915] - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

A stabilized two-phase material point method for hydromechanically coupled large deformation problems - Xiong Tang; Xinpo Li; Siming He (Bulletin of Engineering Geology and the Environment, 2024)

The hepatotoxicity of hexafluoropropylene oxide trimer acid caused by apoptosis via endoplasmic reticulum-mitochondrial crosstalk - Jiayu Du; Xuliang Zhang; Bo Li; Siming Huo; Jian Zhang; Yang Fu; Miao Song; Bing Shao; Yanfei Li (Science of The Total Environment, 2024)

Oral immunization with recombinant L. lactis expressing GCRV-II VP4 produces protection against grass carp reovirus infection - Huiliang Wu; Jiyuan Yin; Siming Li; Hao Wang; Peng Jiang; Pengfei Li; Zhaoyang Ding; Han Yan; Bo Chen; Linchuan Wang; Qing Wang (Fish & Shellfish Immunology, 2024)

Surface addition of Ag on PbO2 to enable efficient oxygen evolution reaction in pH-neutral media - Siming Li; Meng Shi; Chunxia Wu; Kaiqi Nie; Zheng Wei; Xiaopeng Jiang; Xinbing Liu; Huili Chen; Xinlong Tian; Daoxiong Wu; Yawei Li (Chemical Engineering Journal, 2024)

Blocking-baffle mechanism of vegetation to rock avalanche on the forested slope of the east Sichuan-Tibet Mountains - Yong Wu; Zhang-qing Wang; Xin-po Li; Siming He; Xiao-qin Lei (Landslides, 2024)

Hexafluoropropylene oxide trimer acid exposure triggers necroptosis and inflammation through the Wnt/β-catenin/NF-κB axis in the liver - Xuliang Zhang; Bo Li; Siming Huo; Jiayu Du; Jian Zhang; Miao Song; Bing Shao; Yanfei Li (Science of The Total Environment, 2023)

Importance sampling-based probabilistic performance modeling of low-, mid- and high-strength pipelines under coupling effect of hydrogen-induced damage and corrosion - Yihuan Wang; Zhenwei Zhang; Siming Liu; Ailin Xia; Ruiling Li; Guojin Qin (Process Safety and Environmental Protection, 2023)

A 26-week repeated dose toxicity evaluation of sporoderm-removed Ganoderma lucidum spores in rats - Lijuan Xia; Ruimin Sun; Liyan Zhang; Jinrong Li; Chengda Zhang; Qian Yang; Lili Zhang; Siming Zhang; Hanbo Wang; Hanying Lyu; Wanqiang Lyu; Zhenhao Li; et al. (Food and Chemical Toxicology, 2023)

Dibutyl phthalate induces liver fibrosis via p38MAPK/NF-κB/NLRP3-mediated pyroptosis - Siming Huo; Bo Li; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Study on hydrogenation of oxygenated aromatic hydrocarbons via water-gas shift reaction in a subcritical CO-H2O system - Jiale Gu; Huan Li; Wencai Peng; Di Zhu; Jiajia Chen; Shengjie Luo; Siming Liu; Wenxiang Zhao; Youqing Wu; Sheng Huang; Shiyong Wu (Fuel, 2023)

Ingesting retrograded rice (Oryza sativa) starch relieves high-fat diet induced hyperlipidemia in mice by altering intestinal bacteria - Zihang Cheng; Nannan Li; Zhining Chen; Kaikai Li; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Chemistry, 2023)

Genome-resolved metagenomic insight into vanadate and ammonium elimination in sulfur-based autotrophic biosystem - Wenyue Yan; Siming Chen; Min Li; Sitong Liu; Baogang Zhang (Chemical Engineering Journal, 2023)

3D-exosomes laden multifunctional hydrogel enhances diabetic wound healing via accelerated angiogenesis - Han Peng; Huichen Li; Xi Zhang; Jiezhang Tang; Yongping Liang; Lipeng Qiao; Yun Zhu; Mengmeng Hou; Siming Wei; Zhaoxiang Zhang; Chaohua Liu; Xinmao Li; et al. (Chemical Engineering Journal, 2023)

Electrical stimulation promotes synchronous nitrobenzene bio-degradation and vanadate bio-reduction - Siming Chen; Jin Li; Zongyan Li; Shuo Li; Baogang Zhang (Chemical Engineering Journal, 2023)

Shaking table test on a segmental tunnel crossing soil-rock interface under transverse sinusoidal excitations - Siming Li; Yong Yuan; Haitao Yu; Jinghua Zhang; Roberto Cudmani (Tunnelling and Underground Space Technology, 2023)

Review on the development of marine floating photovoltaic systems - Wei Shi; Chaojun Yan; Zhengru Ren; Zhiming Yuan; Yingyi Liu; Siming Zheng; Xin Li; Xu Han (Ocean Engineering, 2023)

Research on the distribution of S species in the pressure oxidation leaching process of SrS solution - Siming Chen; Dongping Duan; Yanjiang Li; Yan Liu; E Zhou (Minerals Engineering, 2023)

Dibutyl phthalate causes heart damage by disrupting Ca2+ transfer from endoplasmic reticulum to mitochondria and triggering subsequent pyroptosis - Bo Li; Siming Huo; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Emissions of formaldehyde and nitrogen dioxide from liquefied petroleum gas combustion - Jin Ye; Siming Shi; Tao Yu; Cong Liu; Jingguang Li; Zhen Ding; Zhijiong Huang; Hua Qian (Process Safety and Environmental Protection, 2023)

Degradation characteristics of intracellular and extracellular ARGs during aerobic composting of swine manure under enrofloxacin stress - Jiaojiao Xu; Jielan Huang; Longhai Chen; Majian Chen; Xin Wen; Pengfei Zhang; Siming Li; Baohua Ma; Yongde Zou; Yan Wang; Xindi Liao; Yinbao Wu (Chemical Engineering Journal, 2023)

Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2023)

Free-standing high-entropy alloy plate for efficient water oxidation catalysis: structure/composition evolution and implication of high-valence metals - Lingya Yi; Siming Xiao; Yunpeng Wei; Dazhi Li; Rongfei Wang; Shengfeng Guo; Weihua Hu (Chemical Engineering Journal, 2023)

Isoalantolactone relieves depression-like behaviors in mice after chronic social defeat stress via the gut-brain axis - Siming Wang; Qihan Cai; Lu Xu; Yanan Sun; Mengmeng Wang; Yu Wang; Lili Zhang; Keqing Li; Zhiyu Ni (Psychopharmacology, 2023)
Rationale The management of depression continues to be challenging despite the variety of available antidepressants. Herbal medicines are used in many cultures but lack stringent testing to understand their efficacy and mechanism of action. Isoalantolactone (LAT) from Elecampane ( Inula helenium ) improved the chronic social defeat stress (CSDS)-induced anhedonia-like phenotype in mice comparable to fluoxetine, a selective serotonin reuptake inhibitor (SSRI). Objectives Compare the effects of LAT and fluoxetine on depression-like behaviors in mice exposed to CSDS. Result The CSDS-induced decrease in protein expression of postsynaptic density (PSD95), brain derived neurotrophic factor (BDNF), and glutamate receptor subunit-1 (GluA1) in the prefrontal cortex was restored by LAT. LAT showed robust anti-inflammatory activity and can lessen the increase in IL-6 and TNF-α caused by CSDS. CSDS altered the gut microbiota at the taxonomic level, resulting in significant changes in α- and β-diversity. LAT treatment reestablished the bacterial abundance and diversity and increased the production of butyric acid in the gut that was inhibited by CSDS. The levels of butyric acid were negatively correlated with the abundance of Bacteroidetes , and positively correlated with those of Proteobacteria and Firmicutes across all treatment groups. Conclusions The current data suggest that, similar to fluoxetine, LAT show antidepressant-like effects in mice exposed to CSDS through the modulation of the gut-brain axis.

Mitophagy alleviates AIF-mediated spleen apoptosis induced by AlCl3 through Parkin stabilization in mice - Miao Song; Jian Zhang; Siming Huo; Xuliang Zhang; Yilong Cui; Yanfei Li (Food and Chemical Toxicology, 2023)

Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles - Ke Zhang; Qing Chen; Jie Xiao; Lijun You; Siming Zhu; Chao Li; Xiong Fu (Food Hydrocolloids, 2023)

Local site effect of soil-rock ground: 1-g shaking table test - Yong Yuan; Siming Li; Haitao Yu; Mingqing Xiao; Ruohan Li; Ruozhou Li (Bulletin of Earthquake Engineering, 2023)

Understanding spatial-temporal travel demand of private and shared e-bikes as a feeder mode of metro stations - Siming Liu; Fan Zhang; Yanjie Ji; Xinwei Ma; Yong Liu; Shuo Li; Xizhen Zhou (Journal of Cleaner Production, 2023)

Hexafluoropropylene oxide trimer acid causes fibrosis in mice liver via mitochondrial ROS/cGAS-STING/NLRP3-mediated pyroptosis - Xuliang Zhang; Jiayu Du; Siming Huo; Bo Li; Jian Zhang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2023)

Substratum virtualization in three-dimensional landslide modeling with the material point method - Shuxi Zhao; Lei Zhu; Wei Liu; Xinpo Li; Siming He; Gianvito Scaringi; Xiong Tang; Yang Liu (Engineering Geology, 2023)

Review of explainable machine learning for anaerobic digestion - Rohit Gupta; Le Zhang; Jiayi Hou; Zhikai Zhang; Hongtao Liu; Siming You; Yong Sik Ok; Wangliang Li (Bioresource Technology, 2023)

Review of biochar production via crop residue pyrolysis: Development and perspectives - Yize Li; Rohit Gupta; Qiaozhi Zhang; Siming You (Bioresource Technology, 2023)

Experimental investigation on the hydrodynamic effects of heave plates used in floating offshore wind turbines - Lixian Zhang; Wei Shi; Yuxin Zeng; Constantine Michailides; Siming Zheng; Ying Li (Ocean Engineering, 2023)

Reconstruction of dynamics processes of Tagharma rock avalanche in Pamir Plateau: Geomorphology and sedimentology implications - Lei Zhu; Siming He; Xiaoqin Lei; Zongji Yang; Jihao Jian; Yi Zhang; Yong Wu; Jiang Li (Engineering Geology, 2023)

T-2 toxin inhibits osteoblastic differentiation and mineralization involving mutual regulation between Wnt signaling pathway and autophagy - Jian Zhang; Peiyan Wang; Miao Song; Xuliang Zhang; Siming Huo; Jiayu Du; Bo Li; Zheng Cao; Yanfei Li (Chemico-Biological Interactions, 2023)

The R2R3-MYB gene CgMYB4 is involved in the regulation of cell differentiation and fiber development in the stamens of Chelone glabra L. - Chunlan Piao; Zhenrui Gao; Siming Yuan; Feifei Li; Min-Long Cui (Protoplasma, 2022)

Refined-JinQi-JiangTang tablet ameliorates hypertension through activation of FGF21/FGFR1 axis in fructose-fed rats - Siming Li; Xiaoling Li; Jing Fan; Xinhang Jia; Hemeng Wang; Fangxin Dong; Haoyang Mao; Chen Zhang; Wenfei Wang; Ye Jiang; Lijun Yan; Na Zhang (Journal of Natural Medicines, 2022)

Energy, economic, and environmental impacts of sustainable biochar systems in rural China - Siming You; Wangliang Li; Weihua Zhang; Hankwon Lim; Harn Wei Kua; Young-Kwon Park; Avanthi Deshani Igalavithana; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2022)

Supplementation of Bacillus sp. DU-106 Alleviates Antibiotic-Associated Diarrhea in Association with the Regulation of Intestinal Microbiota in Mice - Darong Huang; Yanlan Chen; Hongzhu Chen; Xinyu Deng; Jianzhao Huang; Siming Lu; Pan Li; Bing Du (Probiotics and Antimicrobial Proteins, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Mapping the Green-Lipped Mussel (Perna canaliculus) Microbiome: A Multi-Tissue Analysis of Bacterial and Fungal Diversity - Siming Li; Tim Young; Stephen Archer; Kevin Lee; Shaneel Sharma; Andrea C. Alfaro (Current Microbiology, 2022)
Poor health and mortality events of the commercially important and endemic New Zealand green-lipped mussel ( Perna canaliculus ) pose a threat to its industry. Despite the known importance of microbiomes to animal health and environmental resilience, the host-associated microbiome is unexplored in this species. We conducted the first baseline characterization of bacteria and fungi within key host tissues (gills, haemolymph, digestive gland, and stomach) using high-throughput amplicon sequencing of 16S rRNA gene and ITS1 region for bacteria and fungi, respectively. Tissue types displayed distinctive bacterial profiles, consistent among individuals, that were dominated by phyla which reflect (1) a fluid exchange between the circulatory system (gills and haemolymph) and surrounding aqueous environment and (2) a highly diverse digestive system (digestive gland and stomach) microbiota. Gammaproteobacteria and Campylobacterota were mostly identified in the gill tissue and haemolymph, and were also found in high abundance in seawater. Digestive gland and stomach tissues were dominated by common gut bacterial phyla, such as Firmicutes , Cyanobacteria , Proteobacteria , and Bacteroidota , which reflects the selectivity of the digestive system and food-based influences. Other major notable taxa included the family Spirochaetaceae , and genera Endozoicomonas , Psychrilyobacter , Moritella and Poseidonibacter , which were highly variable among tissue types and samples. More than 50% of fungal amplicon sequence variants (ASVs) were unclassified beyond the phylum level, which reflects the lack of studies with marine fungi. However, the majority of those identified were assigned to the phylum Ascomycota . The findings from this work provide the first insight into healthy tissue microbiomes of P. canaliculus and is of central importance to understanding the effect of environmental changes on farmed mussels at the microbial level.

Transcriptome-derived microsatellite markers for population diversity analysis in Archidendron clypearia (Jack) I.C. Nielsen - Dandan Li; Mei Li; Fagen Li; Qijie Weng; Changpin Zhou; Shineng Huang; Siming Gan (Molecular Biology Reports, 2021)

Investigation of the strength recovery characteristics of a red-bed landslide soil by SHS and ultrasonic experiments - Qiwei Yan; Xinpo Li; Xiong Tang; Yong Wu; Siming He (Bulletin of Engineering Geology and the Environment, 2021)

Genetic parameters for growth and Quambalaria shoot blight resistance in Corymbia citriodora subsp. variegata - Shengkan Chen; Jianbo Chen; Guanming Yi; Mei Qin; Shiqi Ren; Ziyu Deng; Qinglan Tang; Dongqiang Guo; Yuanli Zhu; Zhangqi Yang; Chonglu Zhong; Siming Gan; et al. (Euphytica, 2021)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Fracture of rocks in the mountains of Southeast Tibet under hydrothermal conditions at different elevations - Yong Wu; Yongxiang Wang; Waisman Haim; Siming He; Xinpo Li (Bulletin of Engineering Geology and the Environment, 2020)

Numerical assessment of the impeding effect of check dams in the Hongchun debris flow gully, Sichuan Province, China - Wei Shen; Dongpo Wang; Siming He; Tonglu Li (Bulletin of Engineering Geology and the Environment, 2020)

Single-cell transcriptome analysis of the novel coronavirus (SARS-CoV-2) associated gene ACE2 expression in normal and non-obstructive azoospermia (NOA) human male testes - Xixi Liu; Yidong Chen; Wenhao Tang; Li Zhang; Wei Chen; Zhiqiang Yan; Peng Yuan; Ming Yang; Siming Kong; Liying Yan; Jie Qiao (Science China Life Sciences, 2020)

Failure mechanism and dynamic processes of rock avalanche occurrence in Chengkun railway, China, on August 14, 2019 - Lei Zhu; Heng Liang; Siming He; Wei Liu; Qingyun Zhang; Gang Li (Landslides, 2020)

Enhanced correlations of EST-SSR-based genetic distance with hybrid performance, specific hybridizing ability, and heterosis using effect-increasing and effect-decreasing alleles: a case study in Eucalyptus L’Hér. - Shengkan Chen; Changpin Zhou; Xudong He; Qijie Weng; Fagen Li; Mei Li; Yong Guo; Siming Gan (Tree Genetics & Genomes, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Effects of the configuration of a baffle–avalanche wall system on rock avalanches in Tibet Zhangmu: discrete element analysis - YuZhang Bi; SiMing He; YanJun Du; XinPo Sun; XinPo Li (Bulletin of Engineering Geology and the Environment, 2019)

Identification of novel miRNAs and their target genes in Eucalyptus grandis - Zheng Lin; Qingfen Li; Qi Yin; Jinyan Wang; Baolong Zhang; Siming Gan; Ai-Min Wu (Tree Genetics & Genomes, 2018)

Genotypic Variation and Genotype-by-Environment Interactions in Growth and Wood Properties in a Cloned Eucalyptus urophylla × E. tereticornis Family in Southern China - Heyu Yang; Qijie Weng; Fagen Li; Changpin Zhou; Mei Li; Shengkan Chen; Hongxia Ji; Siming Gan (Forest Science, 2018)

Numerical analysis of effect of baffle configuration on impact force exerted from rock avalanches - YuZhang Bi; YanJun Du; SiMing He; XinPo Sun; DongPo Wang; XinPo Li; Heng Liang; Yong Wu (Landslides, 2018)

Data assimilation method based on the constraints of confidence region - Yong Li; Siming Li; Yao Sheng; Luheng Wang (Advances in Atmospheric Sciences, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

Interaction of Wip1 and NF-κB regulates neuroinflammatory response in astrocytes - Fan Xu; Lifei Chen; Xin Zhao; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li (Inflammation Research, 2017)

Genetic parameters for growth and wood mechanical properties in Eucalyptus cloeziana F. Muell. - Changrong Li; Qijie Weng; Jian-Bo Chen; Mei Li; Changpin Zhou; Shengkan Chen; Wei Zhou; Dongqiang Guo; Cuixiang Lu; Jian-Cheng Chen; Dongyun Xiang; Siming Gan (New Forests, 2017)

Two-dimensional landslide dynamic simulation based on a velocity-weakening friction law - Wei Liu; Siming He; Xinpo Li; Qiang Xu (Landslides, 2016)

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway - Haibin Zhong; Ling Cui; Fan Xu; Lifei Chen; Li Jiang; Hui Huang; Jiping Xu; Xin Zhao; Li Li; Siming Zeng; Min Li (Inflammation Research, 2016)

CD200Fc reduces TLR4-mediated inflammatory responses in LPS-induced rat primary microglial cells via inhibition of the NF-κB pathway - Li Jiang; Fan Xu; Wenjing He; Lifei Chen; Haibin Zhong; Yu Wu; Siming Zeng; Li Li; Min Li (Inflammation Research, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Artemisinin mimics calorie restriction to extend yeast lifespan via a dual-phase mode: a conclusion drawn from global transcriptome profiling - DaTing Wang; Ming Wu; SiMing Li; Qian Gao; QingPing Zeng (Science China Life Sciences, 2015)

Fibroblast growth factor (FGF21) protects mouse liver against d-galactose-induced oxidative stress and apoptosis via activating Nrf2 and PI3K/Akt pathways - Yinhang Yu; Fuliang Bai; Yaonan Liu; Yongbi Yang; Qingyan Yuan; Dehua Zou; Susu Qu; Guiyou Tian; Liying Song; Tong Zhang; Siming Li; YunYe Liu; et al. (Molecular and Cellular Biochemistry, 2015)

Seismic Stability of Gravity Retaining Walls Under Combined Horizontal and Vertical Accelerations - Xinpo Li; Lijun Su; Yong Wu; Siming He (Geotechnical and Geological Engineering, 2015)

Up-regulation of SKIP relates to retinal ganglion cells apoptosis after optic nerve crush in vivo - Yu Wu; Fan Xu; Hui Huang; Lifei Chen; Meidan Wen; Li Jiang; Lu Lu; Li Li; Di Song; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Upregulation of Gem relates to retinal ganglion cells apoptosis after optic nerve crush in adult rats - Fan Xu; Hui Huang; Yu Wu; Lu Lu; Li Jiang; Lifei Chen; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Quantitative genetics of cold hardiness and growth in Eucalyptus as estimated from E. urophylla × E. tereticornis hybrids - Xudong He; Fagen Li; Mei Li; Qijie Weng; Jisen Shi; Xiaoyong Mo; Siming Gan (New Forests, 2012)

Study on the rainfall and aftershock threshold for debris flow of post-earthquake - Siming He; Dexin Li; Yong Wu; Yu Luo (Journal of Mountain Science, 2011)

The Role of β20–β21 Loop Structure in Insecticidal Activity of Cry1Ac Toxin from Bacillus thuringiensis - Yuan Lv; Ying Tang; Yunlei Zhang; Liqiu Xia; Faxiang Wang; Xuezhi Ding; Siming Yi; Wenping Li; Jia Yin (Current Microbiology, 2011)

Failure mechanisms of post-earthquake bedrock landslides in response to rainfall infiltration - Yong Wu; Siming He; Yu Luo; Xinpo Li (Journal of Mountain Science, 2011)

Discrete element modeling of debris avalanche impact on retaining walls - Xinpo Li; Siming He; Yu Luo; Yong Wu (Journal of Mountain Science, 2010)

Seismically induced slope instabilities and the corresponding treatments: the case of a road in the Wenchuan earthquake hit region - Xinpo Li; Siming He (Journal of Mountain Science, 2009)

Moderate-Density Molecular Maps of Eucalyptus Urophylla S. T. Blake and E. Tereticornis Smith Genomes Based on RAPD Markers - Siming Gan; Jisen Shi; Mei Li; Kunming Wu; Juying Wu; Jiayu Bai (Genetica, 2003)